Global research priorities in rheumatic fever and rheumatic heart disease - Carapetis Jonathan; Zühlke Liesl (Wolters Kluwer Medknow Publications, 2011)
We now stand at a critical juncture for rheumatic fever (RF) and rheumatic heart disease (RHD) control. In recent years, we have seen a surge of interest in these diseases in regions of the world where RF/RHD mostly occur. This brings real opportunities to make dramatic progress in the next few years, but also real risks if we miss these opportunities. Most public health and clinical approaches in RF/RHD arose directly from programmes of research. Many unanswered questions remain, including those around how to implement what we know will work, so research will continue to be essential in our efforts to bring a global solution to this disease. Here we outline our proposed research priorities in RF/RHD for the coming decade, grouped under the following four challenges: Translating what we know already into practical RHD control; How to identify people with RHD earlier, so that preventive measures have a higher chance of success; Better understanding of disease pathogenesis, with a view to improved diagnosis and treatment of ARF and RHD; and Finding an effective approach to primary prevention. We propose a mixture of basic, applied, and implementation science. With concerted efforts, strong links to clinical and public health infrastructure, and advocacy and funding support from the international community, there are good prospects for controlling these RF and RHD over the next decade.